EFEKTIFITAS PENDAMPINGAN PENGELOLAAN DAN PENGOLAHAN SAMPAH 3 R (REDUCE, REUSE, RECYCLE) TERHADAP MASYARAKAT TERDAMPAK GEMPA BUMI CIANJUR KHUSUSNYA DESA SARAMPAD DAN BENJOT - Fauzan Zikri; Yuliani Yuliani; Melissa Syamsiah; Angga Adriana Imansyah; Adang Suryana; Diny Syarifah Sany (LPPM Universitas Bina Bangsa, 2024)
One of the ways to empower communities affected by the earthquake in Cianjur Regency is through community assistance activities in waste management and processing to create a clean environment. The Suryakancana University lecturer team carried out community service activities in the form of assisting communities affected by the Cianjur earthquake in Sarampad Village and Benjot Village. Forms of mentoring activities are carried out in the form of discussions and practices in processing waste into useful products such as pillows, doormats, fertilizer, and handicrafts. Data collection was carried out through pretest and posttest on 20 respondents (mentoring participants) who came from Sarampad Village and Benjot Village. Mentoring activities will be carried out from August – October 2023. The results of mentoring for earthquake-affected communities from Sarampad Village and Benjot Village show an increase in knowledge, attitudes and skills. Mentoring provided a greater increase in the knowledge aspect compared to the attitude and skills aspect in both Sarampad and Benjot Villages. The increase in knowledge aspects of people affected by the earthquake in Benjot Village (27%) was greater than in Sarampad Village (20%). Meanwhile, in the aspect of attitudes and skills, the increase was greater in the earthquake-affected communities in Sarampad Village (attitudes 18% and skills 17%) than in Benjot Village (attitudes and skills the same 11%).